Gender Analysis in the Outcomes of a Lifestyle Intervention Among Patients Who Had an Open Heart Surgery. (January 2016) - Kadda, Olga; Manginas, Athanasios; Stavridis, George; Balanos, Dimitris; Kotiou, Maria; Panagiotakos, Demosthenes B.
The aim of this study was to evaluate the gender-oriented differences in the outcomes of a lifestyle intervention trial (diet, smoking cessation, and exercise) among patients who had open heart surgery. A randomized, nonblind intervention study was performed on 500 patients who had open heart surgery. Immediately after hospital discharge, 250 patients were randomly allocated lifestyle intervention by receiving oral and written information in the form of a booklet with specific educational information for postoperative rehabilitation. The remaining 250 patients received the regular oral instructions. The applied lifestyle intervention proved to be beneficial only in men as far as quitting smoking (relative risk [RR]: 0.36, confidence interval [CI]: 0.16-0.80; P = .01) and returning to work (RR: 0.35, CI: 0.13-0.92; P = .03) are concerned. For both genders, no significant associations between dietary and physical activity recommendations were observed. Conclusion: Lifestyle nursing intervention immediately after open heart surgery had a beneficial effect on men 1 year after the surgery but not on women. Thus, there is a need for gender-specific studies among women.